Facet effects on generation-recombination currents in semiconductor laser diodes. (1st September 2022) - Fenwick, W E; Deri, R J; Baxamusa, S H; Pope, D L; Boisselle, M C; Dutra, D M; Allen, N P; Crowley, M; Thiagarajan, P; Hosoda, T
Abstract: The contribution of facet defect currents to the overall generation-recombination current of laser diodes operating near 800 nm is quantified experimentally, using the dependence of current on cavity length to isolate facet effects. The results show that facet currents exhibit an ideality factor much greater than 2, while currents associated with the interior of the laser diode stripes exhibit an ideality factor of 2. These differences in behavior provide an approach to infer additional details of defect evolution in aging studies of semiconductor laser diodes.